Analisis Pengungkapan Triple Bottom Line Dalam Penerapan Akuntansi Manajemen Lingkungan Pada Industri Pertambangan - Shella Budiawan (Universitas Gorontalo, 2019)
The purpose of this study is to reveal the Triple Bottom Line in the application of management accounting in the mining industry in Donggala Regency. This research method uses Qualitative Descriptive Method with respondents as many as 30 people who are communities around the location of the company, community leaders, and local government. The analytical tool used in this study is Phenomenology Analysis and data collection techniques carried out by conducting interviews, observation, and documentation to respondents directly.Based on the result of this research shows that company is PT. Balikpapan Ready Mix is not apply yet the concept of Triple Bottom Line in implementation of environment managementaccounting in the company.